Torsion of wandering spleen presenting as acute abdomen: A case report - Surya Prakash; Pankaj Saunakiya; Gouthaman S; Abhishek Kumar Yadav; Sandeep Kumawat (Asian Journal of Medical Sciences, 2024)
Wandering spleen is a very rare condition characterized by the absence or weakness of one or more ligaments holding the spleen in its normal position. “Acquired” wandering spleen may occur during adulthood due to injuries or other underlying conditions that may weaken the ligaments that hold the spleen in its normal position. Torsion of a wandering spleen is an unusual cause of an acute abdomen and is rarely diagnosed preoperatively. Associated torsion of the distal pancreas is even more uncommon. We report a patient with torsion of a wandering spleen and distal pancreas presenting as acute abdomen with lower abdominal lump who was further diagnosed and managed.